Number of leaves for modelling the leaf area of velvet bean according to leaf dimensions - Cargnelutti Filho, Alberto; Toebe, Marcos; Burin, Cláudia; Neu, Ismael Mario Marcio; Alves, Bruna Mendonça (Revista de Ciências Agroveterinárias, 2018)
In order to obtain reliable models for estimating the leaf area, it is important that parameter estimates be accurate and, for that, they must be generated based on an appropriate number of leaves. The objective of this research was to determine the number of leaves required to model the leaf area of velvet beans (Stizolobium cinereum) as determined by digital photos (Y) with regard to the width of the central leaflet limb of the leaf (x), using a potency model (Y=axb), generated through iterative process. In six periods of culture development (29, 43, 57, 73, 87 and 101 days after emergence) were collected, randomly, 790 leaves. Each leaf is composed of left, center and right leaflets. The width of the central leaflet (x) was measured and leaf area (the leaf area sum of the left, center and right leaflets) was determined through the method of digital photos (Y). The number of leaves, necessary for estimating parameters a and b of the potency model and the coefficient of determination (R2), was determined by resampling, with replacement. In the case of the velvet bean, the potency model (Ŷ=4.4019x1.8697, R2=0.9821) based on the width of the central leaflet (x) is adequate to estimate the leaf area obtained through digital photos (Y). Measuring 240 leaves is sufficient to build accurate potency models of the velvet bean leaf area determined by digital photos (Y) with regard to the width of the central leaflet limb of the leaf (x).